Wawasan dan persepsi guru bahasa Indonesia terhadap program pengintegrasian materi anti-KKN dalam pembelajaran bahasa Indonesia - Sumadi, Sumadi (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2012)
Teachers have a very strategic role in combating corruption, collusion, and nepotism in Indonesia, which have reached an alarming level. This can be achieved because, through education, teachers can internalize the values of anti-corruption, collusion, and nepotism to the next generation of the nation in a natural, programmed, and systematic way. This research aims to reveal teachers’ visions and perceptions toward the program of integrating anti-corruption, collusion, and nepotism materials into the Indonesian language teaching–learning process. The results of this research can be used as a starting point for integrating anti-corruption, collusion, and nepotism materials into Indonesian language teaching and learning.